HUBUNGAN RAWAT GABUNG DENGAN MOBILISASI DINI PADA IBU NIFAS HARI PERTAMA DI BPS ENDANG DESA BANARAN KECAMATAN KANDANGAN KABUPATEN KEDIRI - Lestari, Elly Puji (Jurnal AKP, 2010)
Rooming in-system had many advantages. One of them can be used in giving health education to the post partum so they have intention to wake up from bed, keep on their infant and taking care themselves that will quicken mobilization process. Rooming in and early mobilization was very important for post partum health, but there were still many mothers afraid of early mobilization and have not realized the benefits.The goal of this research was to know the correlation of rooming in with early mobilization to the first day post partum in Endang Private Practical Midwife in Banaran Village, Kandangan Sub District, Kediri Regenc.This research was held on January 28 â February 23, 2008. Populations in this research consisted of all the first day post partum in Endang Private Practical Midwife in Banaran Village, Kandangan Sub District, Kediri Regency with samples consisted of 20 respodents. Research design used analytic research design with cross sectional approach. Sampling technique used total sampling, while statistical test used chi-square with significant level 95% or a = 0,05. From research result showed that most of respondents (55%) could implement rooming in with good criteria and implementation of early mobilization, most of them (60%) included in good criteria. From data analysis result showed that x2count > x2table (4,85 > 3,48), so H0 was rejected and H1 was accepted, it meant that there was correlation between rooming in with early mobilization to the first post partum. The intention from mother to wake up from bed as soon as possible because of seeing her infant, intention of mother to take care her infant as soon as possible, and intention of mother in breast feeding her infant caused increase in motherâs motivation to do early mobilization.